The Impact of Macroprudential and Monetary Policies Instruments on the Private Credit Growth in the Arab Banking Sector - Obeid, Rami (International Journal of Economics and Financial Issues, 2023)
This paper investigates the potential impact of macroprudential instruments, namely debt-to-income (DTI) and loan-to-value (LTV) ratios on controlling the private credit growth in the Arab banking system, and we also attempt to examine the effects of the monetary policy instruments on private credit growth by using Generalized Method of Moments (GMM) technique. We measure the effect of loosening or tightening these instruments on the growth of private credit using a sample covers ten Arab countries based on quarterly data for the period (2014-2019). The results reveal that the macroprudential policy tools have the power to control the private credit growth, as the effects of tightening the DTI and the LTV ratios appear directly after one quarter, while the monetary policy tools and the required reserve ratio have a negative impact on the private credit growth, and their effects appear after two quarters and one quarter respectively. Finally, the results show that there is no evidence of significant impact of the economic variables on credit growth.